Umur dan pendampingan suami dengan lama persalinan kala II pada ibu primipara - Yuliza Sofya Wati; Yuni Kusmiyati; Siti Tyastuti (Poltekkes Kemenkes Yogyakarta, 2013)
Maternal mortality rate and neonatal mortality rate in Indonesia are high at 228 per 10o.ooo live births. Maternal mortality in Indonesia caused by prolonged labor 9% which happened by prolonged second stage of labor have high risked for mother and fetus. Prevalence of prolonged labor in Kulon Progo Regency in 2011 occupy highest rank at the rate 12,58%. Based on former study in Wales General Hospital on 2012 number of prolonged second stage of labor is t1% and increased 4.5% at 2011, women in labor and at risked age (>35) are 2,7%. To know the correlation of ages and company of husbands during labor with primipara labor in Wates Kulon Progo General Hospital 2012. This study used an observational with cohort study design. Technik sampling used purposive sampling. To know variable of ages and company of husbands toward variable of labor duration at second stage in women primipara on labor in Wates Kulon Progo General Hospital. There are 64 participants. The result of chi square p-vatu6 0,010 which means there are correlation of ages with prolonged second stage. There are 4 (12,5%) women in labor who accompanied and gave birth more than 2 hours, 87,5% women in labor who accompanied and gave birth less than 2 hours with result p-value 0,000 which means there are significant correlation between company by husband with prolonged second stage. Multivariate analysis used coefficient regression determinant is 0,340. There are correlation of ages and company of husband with prolonged second stage have p-value 0,010. Ages have 4 times risked and company of husband have 12 times risked don’t have prolonged second stage. From coefficient regression determinant can be concluded that variable of prolonged second stage can be explained by variable of ages and company of husband are 34%